Generating Effective Test Suites for Model Transformations Using Classifying Terms - Vallecillo-Moreno, Antonio Jesús; Hilken, Frank; Burgueño-Caballero, Lola; Gogolla, Martin (My University, 2016)
Generating sample models for testing a model transformation is no easy task. This paper explores the use of classifying terms and stratified sampling for developing richer test cases for model transformations. Classifying terms are used to define the equivalence classes that characterize the relevant subgroups for the test cases. From each equivalence class of object models, several representative models are chosen depending on the required sample size. We compare our results with test suites developed using random sampling, and conclude that by using an ordered and stratified approach the coverage and effectiveness of the test suite can be significantly improved.
Keywords: Soporte lógico; Ingeniería del software; Model transformations